Issues in the Legal Theory of USUL and Prospects for Reform. - Mohamad Hashim Kamali (2000)
It is widely accepted within the circle of Islamic jurisprudence that usul al-fiqh has become a theoretical discipline studied as part of the legal heritage rather than a tool to regulate and encourage ijtihad, and usul al-fiqh is not without weaknesses. Some of the weaknesses of usul al-fiqh are not new and had existed for almost as long as usul al-fiqh itself. Even Imam al-Shafi's (d.204H) distinctive contribution to articulate the legal theory of the usl was not devoid of weaknesses. Subsequent developments in the burdened the simplicity of the original approaches to qiyas, ijma' and ijtihad. Another weakness of the legal theory was in its literalist orientations at the expense of goals and purposes of Shari'a (maqasid al-Shari'a). The problem was that the maqasid did not receive much attention for centuries until al-Shatibi (d.790H) wrote his Muwafaqat and opened a new chapter in the methodology of Islamic legal thought. It is the maqasid al-Shari'a that can now utilised to inject flexibility and dynasim into an otherwise ossified methodology. One hardly needs to emphasize that Islam is a Shari'a centered religion and rigidity in the legal theory will have similar consequences for the future of Islam